2019
DOI: 10.14221/ajte.2018v44n5.2
|View full text |Cite
|
Sign up to set email alerts
|

Multiage Education: An Exploration of Advantages and Disadvantages through a Systematic Review of the Literature

Abstract: This systematic quantitative literature review explores existent empirical studies with an interest in multiage education in small school settings, with a specific focus on curriculum and pedagogy. Database searches were methodically conducted across six data bases. The inclusion criteria specified the need for empirical research, and publication dates ranged from 1997 to 2017. The article begins by setting the scene for the systematic review, exploring historical and international practices related to multiag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
5
0
5
Order By: Relevance
“…Auch kann die Jahrgangsmischung zu einer veränderten Inhaltsauswahl und -organisation führen. Ronksley-Pavia et al (2019) unterscheiden zwischen parallelen, rotierenden, spiralförmigen, entwicklungsorientierten und projektbasierten Curricula, die unterschiedliche Effekte auf das Lernen erwarten lassen. Diese Formen spiegeln sich international -im Gegensatz zum deutschen Sprachraum -auch in den Begrifflichkeiten wider (Cornish 2010): Begriffe wie composite classes oder multi-grade classes bezeichnen eher eine pragmatische Umsetzung im Rahmen eines Unterrichts, der Abteilungs-und Frontalunterricht einschließt und sich stark an den jeweils gültigen, einzelnen Jahrgangsstufenlehrplänen orientiert.…”
Section: Lernen In Jahrgangsgemischten Klassenunclassified
See 1 more Smart Citation
“…Auch kann die Jahrgangsmischung zu einer veränderten Inhaltsauswahl und -organisation führen. Ronksley-Pavia et al (2019) unterscheiden zwischen parallelen, rotierenden, spiralförmigen, entwicklungsorientierten und projektbasierten Curricula, die unterschiedliche Effekte auf das Lernen erwarten lassen. Diese Formen spiegeln sich international -im Gegensatz zum deutschen Sprachraum -auch in den Begrifflichkeiten wider (Cornish 2010): Begriffe wie composite classes oder multi-grade classes bezeichnen eher eine pragmatische Umsetzung im Rahmen eines Unterrichts, der Abteilungs-und Frontalunterricht einschließt und sich stark an den jeweils gültigen, einzelnen Jahrgangsstufenlehrplänen orientiert.…”
Section: Lernen In Jahrgangsgemischten Klassenunclassified
“…Auch die Begleituntersuchung zur Schulanfangsphase in Berlin konnte keine generellen Unterschiede aufdecken (Thoren 2017;Thoren und Brunner 2019). International kommen Ronksley-Pavia et al (2019) in ihrem systematischen Review zu empirischen Artikeln für die Jahre 1997 bis 2017 -allerdings nur für kleine Schulen -zu dem unbefriedigenden Ergebnis, dass in manchen Studien keine Unterschiede im Leistungsbereich nachgewiesen werden können, andere Studien mit (kleinen) positiven, wiederum andere mit (kleinen) negativen Entwicklungen aufwarten. Dies deckt sich auch mit älteren Metaanalysen: Veenman (1996) fand K keine signifikanten Unterschiede, Gutiérrez und Slavin (1992) entdeckten positive Effekte auf die Leistung, bei Sundell (1994) und Russel et al (1998) wurden Nachteile des jahrgangsgemischten Lernens für die Leistung festgestellt.…”
Section: Effekte Jahrgangsgemischten Lernens Auf Leistungunclassified
“…For example, Imamzadeh [11] found that multidisciplinary classes were successful and considered as an effective alternative organization to singlegrade classes. And when it comes to impact on student performance, it is important to say that multigrade class organization appears to be much stronger, and the intrinsic performance and efficiency of multigrade students is higher than singlegrade students [12][13][14]. Berry [15] lists four advantages of multigrade teaching, all of them non-cognitive:…”
Section:  Issn:2089-9823mentioning
confidence: 99%
“…In this sense, multigrade schools represent the struggle of education systems to enshrine the right of access to comprehensive education that will enable future generations to acquire and develop knowledge and skills to participate in sustainable development goals and make individual and collaborative decisions based on a commitment to human rights to transform society. UNESCO (2015) considers that this type of schooling helps nations to achieve the mandatory goals of Education for All, and Ronksley-Pavia, Barton and Pendergast (2019) state that these schools are necessary to achieve the fourth goal of Quality Education of the Sustainable Development Programme for 2030.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these schools are small educational centres located in low density populations, where natural environments are one of their main characteristics (Tahull and Montero, 2018). The low enrolment in these schools does not justify the integration of a teacher for each grade; therefore, students attending multigrade schools maintain their grade and the educational materials corresponding to their curriculum, and the teacher is responsible for simultaneously and transversally integrating the contents of the different school grades to cater for the students' chronological diversity, developmental levels and learning styles (Ronksley-Pavia, Barton, and Pendergast, 2019). Hargreaves et al (2001), Little (2001) and Kucita et al (2013) explain how the absence of an education policy and a specialised training for multigrade school teachers is the main cause of the development of decontextualised, traditionalist and conservative teaching practices in these scenarios.…”
Section: Introductionmentioning
confidence: 99%